Equilibrium, kinetic and thermodynamic studies of the adsorption of Congo red on nZVI/Zn-Al layered double hydroxide intercalated with PO4 3− ion - Kofi Duodu; Gerheart Winfred Ashong; Francis Opoku; Nathaniel Owusu Boadi; Eric Selorm Agorku (Discover Sustainability)
Abstract Dyes are among the most hazardous substances used in the world, and the extensive usage of dyes threatens humans and the aquatic environment. In this study, nano zero-valent iron (nZVI), Zn-Al-PO4 and (3–5%) nZVI/Zn-Al-PO4 layered double hydroxides (LDHs) superadsorbents were synthesized using the co-precipitation method. Fourier transform infrared spectroscopy (FTIR), Zetasizer/potential (ZP), scanning electron microscopy (SEM) coupled with electron dispersive X-ray (EDX) and X-ray diffraction (XRD) were employed to study the chemical composition, morphology and structural features of the adsorbent. The adsorbent was applied to remove Congo red (CR) from water through batch adsorption studies. Preliminary investigations show the removal efficiency of 60, 91 and 100% for the Zn-Al-PO4, 3% nZVI/Zn-Al-PO4 and 5% nZVI/Zn-Al-PO4, respectively. An initial concentration of 500 mg/L, LDH dosage of 0.1 g, pH of 6.0, temperature of 313 K and contact time of 80 min were the optimal operation conditions that ensured the maximum removal of CR dye by the 5% nZVI/Zn-Al-PO4 LDH. Kinetic and isotherm studies also revealed that pseudo-second order kinetic and Langmuir isotherm models had the best fit compared to other kinetic and isotherm models employed in this study. The maximum adsorption capacity of CR adsorption on 5% nZVI/Zn-Al-PO4 LDH at the optimal operation conditions was 408.16 mg/g. Thermodynamic studies revealed that ΔG° values were negative at all temperatures, ΔH° was 164.83 kJ/mol and ΔS° was 0.56 kJ/mol, showing that the removal process was spontaneous, endothermic, and had high disorderliness, respectively. Graphical Abstract